Demographic, clinical and biochemical correlates of the length of stay for different polarities in Chinese inpatients with bipolar disorder: A real-world study - Wang, Wei; Du, Jing; Li, Sheng; Xie, Gaoming; Xu, Jinjie; Ren, Yanping (Frontiers in Human Neuroscience, 2023)
Background: Many patients with bipolar illness (BD) need hospitalization, yet there are inadequate psychiatric beds. Managing the length of stay (LOS) is an effective solution to this issue. Research on LOS and its influencing factors in BD is limited in China. This study aimed to identify the factors relevant to LOS in different polarities in Chinese patients with BD. Method: This was a real-world, cross-sectional study. Data were obtained from the electronic medical record system. Patients admitted to Beijing Anding Hospital between Jan 2014 and Dec 2017 and diagnosed with BD were included. Demographic information, clinical characteristics, and biochemical variables were collected. Patients were classified into short and long LOS groups based on a cutoff value. A univariate study and a multivariate logistic regression analysis were performed to identify variables related to LOS in various BD polarities. The receiver operating characteristic (ROC) analysis was utilized to evaluate the discrimination accuracy of the regression model. Result: Four thousand six hundred and seventy-five visits from 4451 unique individuals were included in the analysis. For the whole sample, unmarried status, psychotic features, and family history of mental disorders were positively associated with long LOS (all p < 0.05). There was an additive interaction between a family history of mental disorders and polarities (p < 0.05). For manic episodes, unmarried status, psychotic features, and family history of mental disorders were positively associated with long LOS (all p < 0.05). For depressive episodes, psychotic features and high-density lipoprotein cholesterol (HDLC) levels were positively associated with long LOS (all p < 0.05). For mixed states, unmarried status was positively associated with long LOS, while low-density lipoprotein cholesterol (LDLC) levels were negatively associated with LOS (all p < 0.05). Area under the curve (AUC) values for depressive episodes, manic episodes, and mixed states in the combined model were 0.587, 0.553, and 0.619, respectively (all p < 0.05). Conclusion: The findings suggested that LOS correlates differed by polarity, with marital status, psychotic features, a family history of mental disorders, and lipid levels being strongly linked with LOS in patients with BD.